Allergic Responses Induced by the Immunomodulatory Effects of Nanomaterials upon Skin Exposure - Yoshioka, Yasuo; Kuroda, Etsushi; Hirai, Toshiro; Tsutsumi, Yasuo; Ishii, Ken J. (Frontiers in Immunology, 2017)
Over the past decade, a vast array of nanomaterials has been created through the development of nanotechnology. With the increasing application of these nanomaterials in various fields such as foods, cosmetics, and medicines, there has been concern about their safety, that is, nanotoxicity. Therefore there is an urgent need to collect information about the biological effects of nanomaterials so that we can exploit their potential benefits and design safer nanomaterials, while avoiding nanotoxicity as a result of inhalation or skin exposure. In particular, the immunomodulating effect of nanomaterials is one of most interesting aspects of nanotoxicity. However, the immunomodulating effects of nanomaterials through skin exposure have not been adequately discussed compared with the effects of inhalation exposure, because skin penetration by nanomaterials is thought to be extremely low under normal conditions. On the other hand, the immunomodulatory effects of nanomaterials via skin may cause severe problems for people with impaired skin barrier function, because some nanomaterials could penetrate the deep layers of their allergic or damaged skin. In addition, some studies, including ours, have shown that nanomaterials could exhibit significant immunomodulating effects even if they do not penetrate the skin. In this review, we summarize our current knowledge of the allergic responses induced by nanomaterials upon skin exposure. First, we discuss nanomaterial penetration of the intact or impaired skin barrier. Next, we describe the immunomodulating effects of nanomaterials, focusing on the sensitization potential of nanomaterials and the effects of co-exposure of nanomaterials with substances such as chemical sensitizers or allergens, on the onset of allergy following skin exposure. Finally, we discuss the potential mechanisms underlying the immunomodulating effects of nanomaterials by describing the involvement of the protein corona in the interaction of nanomaterials with biological components and by presenting recent data about the adjuvant effects of well-characterized particle adjuvant, aluminum salt, as an example of immunomodulatory particulate.